Utilization of over-the-counter medicines in medical schemes in South Africa - Padayachee, Neelaveni (My University, 2020)
In South Africa over-the-counter medicines (OTCMs) are freely available to consumers. Medical schemes allow beneficiaries to purchase OTCMs at their discretion via ‘acute medicines benefits’. The primary aim of the study was to explore the utilisation of OTCMs in medical schemes. The dataset was obtained in 2015, from a large medical scheme administrator, providing data for 641 525 beneficiaries. The thesis covers three studies and an article considering ethical issues. The first study focused on the impact of benefit design on utilisation of OTCMs. Two plans were compared, one with rich benefits, the other providing more-restricted benefits. Members accessed OTCMs from the risk pool in the high benefit plan and from a discretionary, day-today benefit in the low benefit plan. Pharmacists and beneficiaries showed a preference for more-expensive generic and original OTCMs, particularly in the rich benefit plan. Doctors prescribed lower-cost products and favoured generics, but also prescribed more-expensive generics or originals to patients in the rich benefit plan. The use of OTCMs did not appear to have an impact on downstream healthcare cost. The second study explored utilisation at a product level, focusing on multi-component analgesic OTCMs, most containing combinations of codeine, paracetamol, caffeine and doxylamine. Unique contributions of this study were that larger pack sizes were dispensed by pharmacists compared to doctors, and no differences were found between doctors who were contracted to the scheme as ‘designated providers’ vs. those who were not. However, dispensing doctors prescribed cheaper and smaller pack sizes of analgesic OTCMs. Of particular note was the large price variation between similarly-constituted products. The third study measured access to commonly-used OTCMs by individuals registered for the management of common chronic diseases via a disease management programme (DMP), and to consider why the medicines were accessed in addition to mainstream drugs prescribed for treatment. There was high utilisation of condition-related OTCMs, most likely to improve uncontrolled disease, or possibly for management of a side-effect of medicines prescribed for treatment of another disease. These OTCMs should be claimed via the risk pool as part of chronic disease management and not paid as ‘discretionary’ benefits. Results indicate that medical schemes and their DMPs are failing to deliver on their mandate. The final paper was based on results of the three studies and considered the ethics around OTCM access: utilisation by individuals; manufacture, marketing and sales; service delivery by doctors and pharmacists; and most importantly, relevant national policies and guidelines. The v conclusion is that OTCMs are behaving as a commodity and not a right. Conclusions and recommendations are presented in the context of three important issues currently being debated in the country: National Health Insurance; the Health Market Inquiry; and amendments to the Medical Schemes Act.
A thesis submitted in fulfilment of the requirements for the degree of Doctor of Philosophy to the Faculty of Health Sciences, University of the Witwatersrand, Johannesburg, 2020